2015
DOI: 10.1007/s11606-015-3399-y
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Diabetes: The Plot Thickens

Abstract: S tatins have now been used in clinical practice for more than 20 years, and are the cornerstone of primary and secondary prevention of cardiovascular disease. The increased risk of new-onset type 2 diabetes in patients treated with statins has been well established by large meta-analyses of randomized controlled trials and observational studies. 1,2 In a meta-analysis of 13 statin intervention trials involving 91,140 participants, statin therapy was associated with a 9 % increased risk of incident diabetes; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Words of caution are in order in that, controversially (Mogadam 2014;Skoumas et al 2018), some of the statins have been suggested in some papers increase the incidence of T2D in patients at risk of that pathology (Macedo et al 2014;Gastaldi and Philippe 2015;Climent et al 2017;Li et al 2018). Indeed, Barkas et al (2020) noted that the greatest risk of statin-caused T2D is in the metabolically unhealthy obese and metabolically unhealthy nonobese patients with statin treated metabolically healthy obese not being at risk of T2D; however, the metabolically healthy obese can, in a non-statin related manner become metabolically unhealthy (Kouvari et al 2019), and so caution with statin use must be exhibited in those moving toward a metabolically unhealthy state even though such is not statin-related.…”
Section: Some Words Of Caution Regarding Certain Hmg-coa Rismentioning
confidence: 99%
“…Words of caution are in order in that, controversially (Mogadam 2014;Skoumas et al 2018), some of the statins have been suggested in some papers increase the incidence of T2D in patients at risk of that pathology (Macedo et al 2014;Gastaldi and Philippe 2015;Climent et al 2017;Li et al 2018). Indeed, Barkas et al (2020) noted that the greatest risk of statin-caused T2D is in the metabolically unhealthy obese and metabolically unhealthy nonobese patients with statin treated metabolically healthy obese not being at risk of T2D; however, the metabolically healthy obese can, in a non-statin related manner become metabolically unhealthy (Kouvari et al 2019), and so caution with statin use must be exhibited in those moving toward a metabolically unhealthy state even though such is not statin-related.…”
Section: Some Words Of Caution Regarding Certain Hmg-coa Rismentioning
confidence: 99%